An insight into the challenges faced by Muslim women entrepreneurs in the hospitality and tourism industry in Malaysia / Saadiah Mohamad, Norlin Nor and Geetha Subramaniam - Mohamad, Saadiah; Nor, Norlin; Subramaniam, Geetha (2010)
This paper reports part of a bigger study on the role of Muslim women entrepreneurs in Small and Medium Enterprises (SME) tourism industry in Malaysia. Essentially it focuses on the challenges, opportunities and business strategies adopted by the Muslim women entrepreneurs in dealing with the challenges of globalisation such as rising global competition posed by the existence of big international chains and fluctuating demand caused by economic uncertainties. The study also explores on whether culture, traditional and religious values are important factors that influence the business practices of these Muslim women entrepreneurs. Interestingly, this paper also describes Malaysian women's participation as employees, managers, and entrepreneurs in the hospitality and tourism industry, as well as the multiple roles the Malaysian families play in relationship to Malaysian women's domestic and hospitality work. Number of women involved in business sector is a growing phenomenon worldwide. Despite this scenario, the involvement of women in business, especially the Muslim women, particularly in the hospitality and tourism industry in Malaysia is not being studied thoroughly and systematically. Many of the researches conducted in the 1980s identified business challenges specific to women entrepreneurs (1). Some of the challenges and difficulties reported included obtaining start-up funds, financial management and development of effective marketing and advertising (2). Other researches also pinpointed that some significant barriers especially financial barriers remained for women establishing and growing businesses (3). Among the list of priority barriers to women entrepreneurship were lack of access to (i) credit; (ii) formal business and social networks; (iii) opportunities to gain management experience and exposure; as well as (iv) the limitations of combining household and family care responsibilities with those running the enterprises, which all could lead to the impact on the growth of women entrepreneurs in the development of SMEs in Malaysia.